Templated Self‐Replication in Biomimetic Systems. Issue 6 (1st April 2019) - Le Vay, Kristian; Weise, Laura Isabel; Libicher, Kai; Mascarenhas, Judita; Mutschler, Hannes
Abstract: A key characteristic of living systems is the storage and replication of information, and as such the development of self‐replicating systems capable of heredity is of great importance to the fields of synthetic biology and origin of life research. In this review, the design and implementation of self‐replicating systems in the context of bottom‐up synthetic biology is discussed, with a particular focus on nucleic acid‐based replication including nonenzymatic systems, ribozyme‐based systems, and complex in vitro translation coupled RNA and DNA replication. The current state and remaining challenges of the respective fields are discussed, and the potential of individual replicators for synthetic biology applications such as the creation of artificial life capable of Darwinian evolution is also summarized. Abstract : The development of self‐replicating systems capable of heredity is of great importance to the fields of synthetic biology and origin of life research. Here, the design and implementation of self‐replicating systems in the context of bottom‐up synthetic biology is discussed, with a particular focus on nucleic‐acid based replication including nonenzymatic, ribozyme‐based, and complex in vitro translation coupled systems.